FACTORS CONNECTED WITH DECISION MAKING OF THE FAMILY IN THE USE OF HEALTH SERVICES AT PUSKESMAS PASIR KALIKI IN 2017 - Indra Karana Napitupulu; Babygia Carolina; Naili Rahmawati (poltekkes kemenkes mataram, 2018)
Abstract: A utilization model of health service influenced by predisposing factors, ability and needs. This study aimed to determine the factors associated with family decision making in the utilization of health services in Kelurahan Pasir Kaliki. The research type was descriptive correlation using Cross Sectional approach. Population in this research was all of population in work area UPT Puskesmas Pasir Kaliki Bandung with 95 responden. Sampling technique that used in this study was purposive sampling. The data were collected by interview using questionnaire. the data were analyzed using Chi Square test. The result showed that respondents who used health service were 84.2%, respondents with high school education 35.8%, 36.8% respondents worked as laborers, 60.0% of respondents have income below UMR and 77,9% respondents who had health insurance. The results of statistical tests show that there is a significant relationship between employments with the utilization of health services. In conclusion, there is a significant correlation between occupational factors with health service utilization (p = 0,034) with estimated risk 0.113. Keywords: Utilization of health service, puskesmas, decision-making, family.